Characterization of chromatin regulators in hepatocellular carcinoma to guide clinical therapy - Jia, Xiangen; Zhang, Guozhi (Frontiers in Genetics, 2022)
Background: Hepatocellular carcinoma (HCC) is notorious for its high mortality and incidence. Accumulating evidence confirms that chromatin regulators (CRs) have a significant impact on cancer. Therefore, exploring the mode of action and prognostic value of CRs is imminent for the treatment of hepatocellular carcinoma. Method: Transcriptome and clinical data for this study have been downloaded from TCGA (https://portal.gdc.cancer.gov/) and ICGC (https://dcc.icgc.org/). Univariate analysis was used to screen CRs with prognostic value, and our prognostic risk score signature was developed using least absolute shrinkage along with selection operator (lasso) Cox regression analysis. The CRs-based prognostic model was constructed in the TCGA dataset, and low-risk HCC patients had a better prognosis, which was finally validated in the ICGC dataset. We used the receiver operating characteristic curve to identify the accuracy of the prediction model and establish a line chart to prove the clinical effectiveness of the model. We also discussed the differences in drug sensitivity via CellMiner database, tumor immune microenvironment via ssGSEA algorithm, and clinical characteristics among different risk groups. Results: A prognostic model consisting of seven CRs was constructed and verified in HCC patients. Furthermore, we found that this risk score prognostic signature could independently predict the prognosis of HCC patients. Functional enrichment analysis revealed that CRs are mainly associated with cancer-related signaling pathways and metabolic pathways. In addition, immune cell abundance correlates with risk score levels Conclusion: In brief, we systematically explored the mode of action of CRs in HCC patients and established a reliable prognostic prediction model.